2006
DOI: 10.1210/jc.2005-2532
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Human Pituitary Tumor-Transforming Gene Immunohistochemical Expression in Differentiated Thyroid Cancer

Abstract: Immunohistochemical analysis of hPTTG is of potential value in the determination of tumor aggressiveness in DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
2
37
0
1
Order By: Relevance
“…PTTG and PBF downregulate NIS expression and iodide uptake in vitro We and others have previously demonstrated that thyroid cancers show increased expression of PTTG Boelaert et al, 2003a;Saez et al, 2006), and we recently reported that PBF is also overexpressed in differentiated thyroid tumours compared with normal tissue . In addition, two reports have indicated that PTTG represses NIS and that PTTG protein expression is negatively correlated with radioiodine uptake in thyroid tumours (Saez et al, 2006).…”
Section: Nis Expression Is Reduced In Thyroid Cancermentioning
confidence: 69%
See 3 more Smart Citations
“…PTTG and PBF downregulate NIS expression and iodide uptake in vitro We and others have previously demonstrated that thyroid cancers show increased expression of PTTG Boelaert et al, 2003a;Saez et al, 2006), and we recently reported that PBF is also overexpressed in differentiated thyroid tumours compared with normal tissue . In addition, two reports have indicated that PTTG represses NIS and that PTTG protein expression is negatively correlated with radioiodine uptake in thyroid tumours (Saez et al, 2006).…”
Section: Nis Expression Is Reduced In Thyroid Cancermentioning
confidence: 69%
“…In addition, two reports have indicated that PTTG represses NIS and that PTTG protein expression is negatively correlated with radioiodine uptake in thyroid tumours (Saez et al, 2006). We therefore investigated whether PTTG and PBF can repress NIS expression and iodide uptake in primary thyroid cells in vitro.…”
Section: Nis Expression Is Reduced In Thyroid Cancermentioning
confidence: 95%
See 2 more Smart Citations
“…PTTG overexpression was found to decrease iodide uptake in both rat thyroid FRTL-5 cells and human primary thyroid cells, and NIS expression was reduced in the human thyrocytes ). More recently, high PTTG expression has significantly been associated in vivo with decreased radioiodine uptake during patient follow-up (Saez et al 2006). The initial observation that PTTG may be involved in the regulation of iodide uptake led us to investigate the possibility of a similar role for PBF.…”
Section: Pbf and Iodide Uptakementioning
confidence: 99%